Government Strategy in Political Education as Public Participation Improvement to Reach Democracy System in Semarang City - Suparno, Suparno; Karmanis, Karmanis; Sunaryo, Alexius (Political Science Program, Universitas Negeri Semarang, 2020)
Republic of Indonesia is a democratic country which means all matters in the country must be based on the wishes of the people. Successful democracy in a country can be judged by the implementation of direct, general, free, and secret elections. The people have the right to determine their government so that people have valuable values in a democratic country. In this study, researchers formulated the government strategy in political education as an effort to increase public participation in realizing a democratic system in Semarang City. This research used a descriptive qualitative method. This research was conducted in Semarang City, Central Java. The implementation of a political education by the Semarang City government has not been maximized. Based on the results of the research, the provision of information for the implementation of public political participation, especially the young age grouphas not been running optimally. Second, the Media (political parties) as an aggregation of the public interests, must be more active in building communication systems, one of which is by gathering public aspirations in public consultation forums. Third, the implementation of political activities are in various methods, such as social activities, seminars, studies, socialization and training, and coaching, those implementations are determined according to the right conditions, scheduled and routine, but do not rule out the possibility of activities adapted to existing conditions.